An insight to kidney dialysis treatment - Subhan, Amber; Siddharth, Lolla; Saba, Samarin; Khanam, Safura; Goud, Mudimala Rekha (International Journal of Basic & Clinical Pharmacology, 2025)
The kidneys are a pair of crucial organs that perform multiple functions in maintaining the cleanliness and chemical balance of blood. The two most common causes of kidney damage are high blood pressure and diabetes. The national kidney foundation recommends three simple tests: a blood pressure check, a spot check for protein or albumin in the urine, and calculation of glomerular filtration rate (GFR) based on a serum creatinine measurement. Ridding the blood of waste and extra water is done through the procedure of dialysis. It is basically used in patients with renal failure to create an artificial substitute for the lost kidney function. End-stage renal disease (ESRD) is a condition other referred to as ESRD, referring to complete or almost complete, irreversible kidney failure. If treatment is not received, uremia can cause a coma, seizures, and death. Patients may require dialysis or a kidney transplant if both kidneys fail completely.